Physico-mechanical Properties of Date Palm Leaf Particle Board - Ghosh, S K; Nayak, L K; Bhattacharya, S K (Journal of Agricultural Engineering, 2006)
Particle board of different sizes (150x 150 x 12.5) mm, (250 x 250 x 12.5) mm and (600 x 600 x 12.5) mm, both on bench scale and on large scale basis was prepared from Date-palm leaves, Phoenix Dactylifera L, the renewable agrowaste, having ultimate fibre length of 1.25 - 2.50 mm and a cellulose content of about 60%. Two types of synthetic resins (Urea Formaldehyde and Phenol Formaldehyde) were used in various concentrations. The physico-mechanical properties viz. density, average thickness, swelling in water, impact strength, tensile strength of the boards were measured and compared with that of the jute stick particle board and wood board. Boards prepared using the PF resin showed higher mechanical properties and low swelling in water as compared to other particle boards. The treatment with 1.5% paraffin wax (used as the water repellent chemical) reduced the swelling of the boards in the water.